Paleopathology – Development, Achievements and Purpose - Gładykowska-Rzeczycka, Judyta (Anthropological Review, 1993)
This paper presents a history of the development of paleopathology. The discussion is divided into three parts: changes in the objects, methods and subject matter. First, changes in the nature of the subjects that were analyses are reviewed. In the eighteenth century these objects were animal bones; in the nineteenth century they took the form of mummies and skulls; and in the twentieth century, as well as postcranial bones, old written sources such as papyri and the bible were studied along with works of art. Second, the method changed from being mainly macroscopic in the early stages to the use of scanning and electronic microscopes, tomography, etc in more recent times. Third, the subject matter and the form of the elaboration of disease has changed from the description of a single case of, for example, trauma, syphilis or inflammatory diseases to the synthetic presentation of diseases such as leprosy and tuberculosis. This paper underlines the great achievement of American paleopathologists within the last thirty years. They were responsible for organising the Association of Paleopathology, many seminars and meetings and the Newsletter of Paleopathology. The achievements and possibilities of Polish paleopathology are presented and the main problems facing world paleopathology are also outlined.